Evaluation and management of the hypertensive phase following Ahmed glaucoma valve implantation - Gonçalves, Ana Sofia Lopes (2019)
Purpose: To analyze the hypertensive phase (HTP) in patients undergoing Ahmed glaucoma valve (AGV) implantation. Material and Methods: Retrospective study of 26 patients (valves) undergoing AGV implant with a follow-up ≥1 year. The HTP was defined as an intraocular pressure (IOP) ≥22 mmHg within 3 months after surgery, after an initial reduction of IOP to <22mm Hg during the 1st postoperative week, and not caused by tube obstruction, retraction or dysfunction. The sample was divided into group with (group 1) and without (group 2) HTP. The parameters were: group 1 – prevalence and period of time up to the HTP, maximum IOP and number of hypotensors and HTP management; comparison between groups – the most prevalent type of glaucoma, evolution of the IOP and of the number of hypotensors during the follow-up and surgical success in the 1st year. Results: HTP was observed in 59% of the cases, mainly at the 1st month (68%), with an average IOP peak of 28.05±5.4 mmHg and the maximum number of hypotensors during the follow-up of 3.1±0.7. The most prevalent type of glaucoma for group 1 was uveitis (44.4%) and for group 2 were primary open-angle glaucoma and neovascular glaucoma (both 34%). The mean pre and postoperative values ​​at the last IOP and medication number were higher for group 1. This group also included injection of 5-fluorouracil, needling and bleb excision. The overall surgical success was 89% in group 1 and 100% in group 2. Statistically significant differences were: IOP and number of hypotensors between the 1st and the 6th month after surgery, and complete surgical success at the 1st year. Conclusions: The identification of HTP is essential, as it is associated with a higher IOP, number of hypotensors and surgical procedures, with a potential impact on the prognosis.